The Role of Ecotourism in Regional Development in Theory-Practice Axis: the Case of Sapanca - YILMAZ, Tuğba; Boztaş, Asena; Yılmazer, Aydın; AKGÜN, Sibel (Anais Brasileiros de Estudos Turísticos, 2021)
Development theories are described as a comprehensive philosophy that underpins development policies. Tourism, which is used as a development tool for developing countries, is a field that is influenced by developmental theories and shaped by the perspectives of these theories. Therefore, understanding development theories is important for understanding the development process of tourism. This study was carried out in Turkey which is one of the countries where ecotourism is used as a development tool. In this context, Turkey’s emerging ecotourism area of Sapanca, which is defined as the study of the universe and the new regionalism theory shaping tourism policy aimed to investigate the reflections of real life through ecotourism. In this regard, a questionnaire answered by 395 local people were matched for the reflection of regional development theories in the region base on the theory and practice. From the research results, it was concluded that ecotourism policies prepared under the new regionalism theories have a positive effect on the development of the region. Therefore, the answers of the questionnaire has proved that ecotourism has been successfully applied within the scope of the new regionalism theory in the regional development of Sapanca both in theory and practice. Key words: Regional Development; Ecotourism; Regional Development Theory; Sapanca; Turkey.